If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -9 = 11x + -15 Reorder the terms: -9 + 5x = 11x + -15 Reorder the terms: -9 + 5x = -15 + 11x Solving -9 + 5x = -15 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -9 + 5x + -11x = -15 + 11x + -11x Combine like terms: 5x + -11x = -6x -9 + -6x = -15 + 11x + -11x Combine like terms: 11x + -11x = 0 -9 + -6x = -15 + 0 -9 + -6x = -15 Add '9' to each side of the equation. -9 + 9 + -6x = -15 + 9 Combine like terms: -9 + 9 = 0 0 + -6x = -15 + 9 -6x = -15 + 9 Combine like terms: -15 + 9 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| -4(3p+3)-18=3(4p+6) | | 2y(y+4)=10 | | -71+15y+3=5(5y-4)-8 | | 6(c-7)=7(c-8) | | -3(6n-6)+3n= | | 19=6x-11 | | 3(2a-5b+6)= | | 7t-t-6=5t-5 | | -15=15(h-2) | | b^2=3b | | 6t-t-3=4t-4 | | 105-90=32y-37y | | -720=-20(-4b) | | (m)=8 | | 3s^2=7s | | 4y-7y=12 | | (2t+5)=3 | | 7-7=10t-3t | | 12s-14s=8 | | y+2.3=5.6 | | -17x=255 | | y-2=0 | | -2+13=6b-3-5b | | b^4-1296= | | 4x^3=9x^2 | | 10=z+3 | | 5(x-7)=10 | | 5+3(4n+2)-n= | | m-3=8 | | 40=1.6m | | 3x+7-2=8 | | 2.3g=7.13 |